2020
DOI: 10.1111/cogs.12809
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of Language Transfers From Speech to Sign: Evidence From Doubling

Abstract: Does knowledge of language transfer across language modalities? For example, can speakers who have had no sign language experience spontaneously project grammatical principles of English to American Sign Language (ASL) signs? To address this question, here, we explore a grammatical illusion. Using spoken language, we first show that a single word with doubling (e.g., trafraf) can elicit conflicting linguistic responses, depending on the level of linguistic analysis (phonology vs. morphology). We next show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…For example, in one line of research, we found that speakers with no command of a sign language spontaneously project the phonological and morphological principles from their spoken language to dynamic linguistic signs. Critically, responses to linguistic signs varied systematically, depending on the structure of speakers’ spoken language (e.g., Berent et al, 2016 , 2021 ; Berent, Bat-El, et al, 2020 ). As such, these results suggest that the knowledge that participants invoked must have been at least partly disembodied and abstract.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in one line of research, we found that speakers with no command of a sign language spontaneously project the phonological and morphological principles from their spoken language to dynamic linguistic signs. Critically, responses to linguistic signs varied systematically, depending on the structure of speakers’ spoken language (e.g., Berent et al, 2016 , 2021 ; Berent, Bat-El, et al, 2020 ). As such, these results suggest that the knowledge that participants invoked must have been at least partly disembodied and abstract.…”
Section: Discussionmentioning
confidence: 99%
“…Other arguments for abstraction are presented by the convergence of phonological principles across sensory modality—spoken and manual (e.g., Andan et al, 2018 ; Brentari, 2011 ; Sandler & Lillo-Martin, 2006 ). And indeed, speakers who are ASL-naive demonstrably project grammatical principles from their spoken language to ASL signs (e.g., Berent et al, 2016 , 2021 ; Berent, Bat-El, et al, 2020 ). Such results suggest that some phonological principles are independent of language modality.…”
Section: Introductionmentioning
confidence: 99%